Antimicrobial Prescribing and Stewardship, 2nd Volume - Ashiru-Oredope, Diane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The second volume of the Special Issue entitled "Antimicrobial Prescribing and Stewardship" consists of manuscripts, including original research articles, review articles, and opinion papers regarding antimicrobial stewardship-related topics, including disease-based/organism-based antimicrobial stewardship; the influence of antimicrobial utilization changes on antimicrobial resistance; the impact of antimicrobial stewardship on quality performance measures and patient outcomes; novel antimicrobial stewardship education and training approaches or interventions aimed toward the public and/or healthcare workers; behavioral change approaches to antimicrobial stewardship; collaborative practice agreements in antimicrobial stewardship; antimicrobial stewardship in special populations (e.g., pediatrics, geriatrics, emergency medicine, hematology/oncology); tackling AMR through antimicrobial stewardship in low- and middle-income countries; antimicrobial stewardship for animal health; antimicrobial stewardship in alternative settings (e.g., community practice, long-term care, resource-limited settings, small and rural hospitals); antimicrobial use and stewardship in the context of the COVID-19 pandemic; and global collaborations to tackle AMR through antimicrobial stewardship.